Pola Kepemimpinan Kepala Desa Balunijuk Kecamatan Merawang Kabupaten Bangka Periode 2017-2023 - Aryani, Novia; Murtasidin, Bahjatul; Hidayat, Novendra (Journal of Politics and Democracy, 2024)
Leadership pattern refers to the specific approach employed by a leader to effectively influence and guide their subordinates, ensuring that their actions align with the leader's objectives and desires. Every leader possesses a distinct leadership style when it comes to overseeing their respective domain. Therefore, this study examines the leadership pattern of the Headman of Balunijuk Village, Merawang District, Bangka Regency for the 2017-2023 period. This study used a qualitative research method with a descriptive approach The types and sources of data utilized in this study were primary and secondary data Meanwhile, data collection techniques were interviews, observation, and documentation. This research employs Heywood's (2000) political leadership theory. The results showed that Suwandi, as the Balunjuk Village Headman for the 2017-2023 period, has carried out leadership well. The Balunjuk Village Headman consistently demonstrated political leadership during the 2017-2023 period. The Headman is renowned for possessing admirable qualities such as excellent character, politeness, friendliness, and a nurturing approach to leadership This is clearly demonstrated by the village headman's track record and experience leading Balunjuk Village from 2017 to 2023. Second, the village headman prioritizes leadership as a personal attribute to maintain discipline and address issues. This involves effective coordination between the leader, administrative staff, the community, and other relevant parties who possess the necessary expertise to make informed decisions regarding specific matters that arise during the leader's tenure This approach guarantees the resolution of problems through meticulous deliberation. Third, during 2017-2023, the village headman demonstrated leadership as a political virtue by effectively communicating with the personnel in the village office, ensuring that each staff member fulfilled their respective roles and responsibilities Hence, effective leadership requires an approach that involves clear communication and coordination with the device staff regarding their assigned activities, functions, and responsibilities. This ensures that they are able to fulfill their obligations in a competent manner.